Pullulan-based films impregnated with silver nanoparticles from the Fusarium culmorum strain JTW1 for potential applications in the food industry and medicine - Wypij, Magdalena; Rai, Mahendra; Zemljič, Lidija Fras; Bračič, Matej; Hribernik, Silvo; Golińska, Patrycja (Frontiers in Bioengineering and Biotechnology, 2023)
Introduction: Biopolymers, such as pullulan, a natural exopolysaccharide from Aureobasidium pullulans, and their nanocomposites are commonly used in the food, pharmaceutical, and medical industries due to their unique physical and chemical properties. Methods: Pullulan was synthesized by the A. pullulans ATCC 201253 strain. Nanocomposite films based on biosynthesized pullulan were prepared and loaded with different concentrations of silver nanoparticles (AgNPs) synthesized by the Fusarium culmorum strain JTW1. AgNPs were characterized by transmission electron microscopy, Zeta potential measurements, and Fourier-transform infrared spectroscopy. In turn, the produced films were subjected to physico-chemical analyses such as goniometry, UV shielding capacity, attenuated total reflection–Fourier-transform infrared spectroscopy, scanning electron microscopy, and X-ray photoelectron spectroscopy, and their mechanical and degradation properties were assessed. The antibacterial assays of the nanoparticles and the nanocomposite films against both food-borne and reference pathogens, including Listeria monocytogenes, Salmonella infantis, Salmonella enterica, Escherichia coli, Staphylococcus aureus, Pseudomonas aeruginosa, and Klebsiella pneumoniae, were performed using standard methods. Results: AgNPs were small (mean 15.1 nm), spherical, and displayed good stability, being coated with protein biomolecules. When used in higher concentrations as an additive to pullulan films, they resulted in reduced hydrophilicity and light transmission for both UV-B and UV-A lights. Moreover, the produced films exhibited a smooth surface. Therefore, it can be concluded that the addition of biogenic AgNPs did not change the morphology and texture of the films compared to the control film. The nanoparticles and nanocomposite films demonstrated remarkable antibacterial activity against both food-borne and reference bacteria. The highest activity of the prepared films was observed against L. monocytogenes. Discussion: The obtained results suggest that the novel nanocomposite films prepared from biosynthesized pullulan and AgNPs can be considered for use in the development of medical products and food packaging. Moreover, this is the first report on pullulan-based nanocomposites with mycogenic AgNPs for such applications.